Effect of chlorhexidine gluconate on mechanical and anti-microbial properties of thermoplastic cassava starch. (1st January 2022) - Thajai, Nanthicha; Jantanasakulwong, Kittisak; Rachtanapun, Pornchai; Jantrawut, Pensak; Kiattipornpithak, Krittameth; Kanthiya, Thidarat; Punyodom, Winita
Abstract: Antimicrobial thermoplastic starch (TPS) was developed using cassava starch, glycerol, and chlorhexidine gluconate (CHG) blend. CHG was added at concentrations of 1%, 5%, 10%, and 20% (wt./wt.) as an antimicrobial additive. The tensile strength and hardness of the blended samples increased with the chlorhexidine gluconate content, especially for 1% CHG. wt./wt. (12.6 MPa and 94, respectively). The TPS/CHG20 blend exhibited a large phase of CHG and recrystallization of TPS. The water solubility decreased with the addition of CHG. Nuclear magnetic resonance data confirmed a reaction between the hydroxyl groups of TPS and the amino groups of CHG. The TPS/CHG20% exhibited an inhibition zone for three bacterial types ( Staphylococcus aureus, Escherichia coli, and Bacillus cereus ) and three fungal types ( Rhizopus oligosporus, Aspergillus oryzae, and Candida albicans ). CHG acted simultaneously as a chain extender and an antimicrobial additive for TPS, improving its tensile strength, hardness, and anti-microbial properties. Highlights: Antimicrobial thermoplastic starch (TPS) using chlorhexidine gluconate (CHG) CHG acted as a dual chain extender and antimicrobial for TPS. Mechanical properties of TPS were improved by CHG addition. NMR confirmed a reaction between TPS and CHG. The TPS/CHG20% inhibited three bacterium and three fungus types.